FLUORITE SOLUBILITY IN HYDROUS HAPLOGRANITIC MELTS AT 100 MPA - Dolejš D.; Baker D.R. (My University, 2006)
Fluorite is the most common fluoride mineral in magmatic silicic systems and its crystallization can moderate or buffer fluorine concentrations in these settings. We have experimentally determined fluorite solubility and speciation mechanisms in haplogranitic melts at 800-950 °C, 100 MPa and aqueous-fluid saturation. The starting haplogranite compositions: peraluminous (alumina saturation index, ASI = 1.2), subaluminous (ASI = 1.0) and peralkaline (ASI = 0.8) were variably doped with CaO or F2O-1 in the form of stoichiometric mineral or glass mixtures. The solubility of fluorite along the fluorite-hydrous haplogranite binaries is low: 1.054 ±0.085 wt.% CaF2 (peralkaline), 0.822 ± 0.076 wt.% (subaluminous) and 1.92 ± 0.15 wt.% (peraluminous) at 800 °C, 100 MPa and 10 wt.% H2O, and exhibits a minimum at ASI~1. Fluorite saturation isotherms are strongly hyperbolic in the CaO+cF2O-1 space, suggesting that fluorite saturation is controlled by the activity product of CaO and F2O-1, i.e., these components are partially decoupled in the melt structure. The form of fluorite liquidus isotherms implies distinct roles of fluorite crystallization: in Ca-dominant systems, fluorite crystallization is controlled by the fluorine concentration in the melt only and remains nearly independent of calcium contents; in F-rich systems, the crystallization of fluorite is determined by CaO contents and it does not buffer fluorine concentration in the melt. The apparent equilibrium constant, K, for the equilibrium CaO + cF2O-1 = CaF2 (+ associates) is log K = -(2.449 ± 0.085) · Al2O3exc + (4.902 ± 0.066); the reaction-stoichiometry parameter varies as follows: c = -(0.92 ± 0.11) · Al2O3exc + (1.042 ± 0.084) at 800 °C, 100 MPa and fluid saturation where Al2O3exc are molar percent alumina in excess over alkali oxides. The reaction stoichiometry, c, changes at subaluminous composition: in peralkaline melts, competition of other network modifiers for excess fluorine anions leads to the preferential alkali-F short-range order, whereas in peraluminous compositions, excess alumina associates with calcium cations to form calcioaluminate tetrahedra. The temperature dependence of fluorite solubility is described by the binary symmetric Margules parameter, W = 36.0 ± 1.4 kJ (peralkaline), 39.7 ± 0.5 kJ (subaluminous) and 32.8 ± 0.7 kJ (peraluminous). The strong positive deviations from ideal mixing imply the occurrence of CaF2-granite liquid-liquid immiscibility at temperatures above 1258 °C, which is consistent with previous experimental data. These experimental results suggest very low solubilities of fluorite in Ca-rich melts, consistent with the lack of fluorine enrichment in peralkaline rhyolites and calc-alkaline batholiths. On the other hand, high CaO concentrations necessary to crystallize fluorite in F-rich peraluminous melts are not observed in nature and thus magmatic crystallization of fluorite in topaz-bearing silicic suites is suppressed. A procedure for calculating fluorite solubility and the liquidus isotherms for a whole-rock composition and temperature of interest is provided. © 2005 Elsevier B.V. All rights reserved.
Keywords: CRYSTALLIZATION; FLUORITE; GRANITE; MELT; RHYOLITE; THERMODYNAMICS